PEA2SnBr4: a water-stable lead-free two-dimensional perovskite and demonstration of its use as a co-catalyst in hydrogen photogeneration and organic-dye degradation. Issue 27 (1st July 2020) - Romani, Lidia; Bala, Anu; Kumar, Vijay; Speltini, Andrea; Milella, Antonella; Fracassi, Francesco; Listorti, Andrea; Profumo, Antonella; Malavasi, Lorenzo
Abstract : A novel 2D lead-free perovskite showing stability in water and providing efficient hydrogen photogeneration. Abstract : A novel lead-free 2D perovskite, namely PEA2 SnBr4, shows impressive water-resistance by retaining its original crystal structure and optical properties when placed in contact with water. Such key properties have been advantageously used for the fabrication of a novel co-catalytic system by coupling PEA2 SnBr4 with graphitic carbon nitride. PEA2 SnBr4 /g-C3 N4 composites at different metal halide perovskite loadings (5 and 15 wt%) have been prepared and tested in hydrogen photogeneration in an aqueous environment and organic dye degradation (methylene blue). The results show an impressive enhancement of H2 production of the composite with respect to the two separate components with hydrogen evolution rates up to 1600 μmol g −1 h −1 and analogous improvements in the efficiency of methylene blue degradation. The present results, providing a novel water-resistant perovskite and co-catalytic system, pave the way towards the safe, efficient and real use of metal halide perovskites in catalysis.